Encyclopedia of Life Sciences 2009
DOI: 10.1002/9780470015902.a0001685.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Plant Microtubules: Their Role in Growth and Development

Abstract: The close association of cortical microtubules with cell walls is a characteristic of immobile plant cells. In interphase, the cortical array helps organize the cell wall and before division is replaced by a narrower preprophase band that forecasts where the new cross‐wall will be attached after mitosis. The mitotic spindle is essentially similar to the general eukaryotic model but the lack of centrosomes at the poles means that the plant spindle looks different, having broader poles and reduced astral microtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In this section we consider the orientation of the array as measured by the order parameter 2 . Cells within a single type of tissue often show a similar degree of alignment and orientation of their cortical array [31], which indicates that the process of array formation is robust and repeatable. On the other hand, external triggers such as light [2], hormones [32], and mechanical cues [33,34] are able to modify the array orientation, illustrating that the process is susceptible to orientational cues, which may in turn be subject to cellular control.…”
Section: Effect Of Cell Geometry and Local Changes In Microtubule Dynmentioning
confidence: 99%
“…In this section we consider the orientation of the array as measured by the order parameter 2 . Cells within a single type of tissue often show a similar degree of alignment and orientation of their cortical array [31], which indicates that the process of array formation is robust and repeatable. On the other hand, external triggers such as light [2], hormones [32], and mechanical cues [33,34] are able to modify the array orientation, illustrating that the process is susceptible to orientational cues, which may in turn be subject to cellular control.…”
Section: Effect Of Cell Geometry and Local Changes In Microtubule Dynmentioning
confidence: 99%
“…Recent studies have revealed that cell shape may have influence on the orientation of the CA [ 4 ]. On the other hand, the orientation of the CA controls cell expansion and cell anisotropy, by guiding the deposition of cellulose synthase complexes along the MTs [ 5 8 ]. Through this coupling, the CA in turn can influence the cell shape, essentially setting up a morphogenetic feedback loop.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that cell shape may have influence on the orientation of the CA 4 . On the other hand, the orientation of the CA controls cell expansion and cell anisotropy, by guiding the deposition of cellulose synthase complexes along the MTs [5][6][7][8] . Through this coupling, the CA in turn can influence the cell shape, essentially setting up a morphogenetic feedback loop.…”
Section: Introductionmentioning
confidence: 99%